SENTRA PINDANG KUSAMBA SEBAGAI PUSAT TRADISI PEMINDANGAN DAN IDENTITAS GASTRONOMI PULAU DEWATA - Dwik Suwarnata Triana (CV. Lafadz Jaya, 2026)
The Kusamba Salted-Boiled Fish (Pindang) Center faces challenges in sustaining its tradition amid fluctuating fish catches, market pressures, and hygiene demands, while also carrying a symbolic role in shaping Bali's culinary image. This study aims to examine how the practices, meanings, and values of pindang production in Kusamba shape Balinese gastronomic identity and to affirm Kusamba's position as a center of tradition. A descriptive qualitative method with an ethnogastronomic approach was applied through participant observation, in-depth interviews, process documentation, and mapping of the food chain from upstream to downstream; data were analyzed thematically. The results show a concentration of practitioners and a coordinated production rhythm, from fish selection to packaging; the existence of unwritten taste standards maintained through collective work; and a consistent sensory profile characterized by clean saltiness, firm yet moist flesh, and a sea aroma balanced with spices. Work organization is structured around a hierarchy of experience and a shared